Notes on The Rubiaceae. 4: Five New Records for Bangladesh - Das, Sujit C; Dev, Pradip K; Rahman, M Atiqur (Bangladesh Journal of Botany, 2012)
The occurrence of five species namely, Mussaenda keenani Hook. f., Mycetia listeri Deb, Ophiorrhiza fasciculata D. Don, Psychotria stipulacea Mail. and Psydrax umbellata (Wight) Bridson, of the family Rubiaceae in the flora of Bangladesh is reported for the first time. The Psydrax Gaertn. is also a new generic record for Bangladesh. These species are described along with their ecology, geographical distribution and places of occurrence in Bangladesh. Illustrations and photographs of these new records are also provided. DOI: http://dx.doi.org/10.3329/bjb.v41i1.11078 Bangladesh J. Bot. 41(1): 21-28, 2012 (June)